The Effects of Turmeric Infusion and Turmeric Juice (Curcuma Domestica) on The Staphylococcus Aureus Growth in Vitro - Puspitasari, Renny Novi; Handayani, Handayani; Sofaria, Ratna (UNUSA Press, 2021)
Background: Turmeric is a plant that grows in tropical areas and functions as medicine. The chemical compounds contained in turmeric have a role as antioxidants, antimicrobials, anti-cancer, indigestion, smallpox, insect bites. The curcumin content in turmeric has antibacterial activity against various types of Gram negative, Gram positive, antiviral and anti-tumor bacteria. Essential oils can be used as antibacterial because they contain hydroxyl and carbonyl functional groups which are phenol derivatives. Flavonoids can interfere with cell wall formation with peptidoglycan transpeptidase activity which will break down cell walls and damage cell membranes so that important components such as proteins, nucleic acids, nucleotides will be lysis. Staphylococcus bacteria are normal flora on the skin, respiratory tract, and digestive tract of food in humans. These bacteria can cause disease when they reach 1,000,000 or 106 per gram, an amount sufficient to produce the toxin. S. aureus bacteria can cause various types of infections ranging from minor skin infections, food poisoning to systemic infections. The aim of our study was to analyze the effects of infusion and turmeric juice (Curcuma domestica val) on the growth of bacteria Staphylococcus aureus through invitro. Method: This study is a laboratory experimental study with the aim of analyzing turmeric infusion (Curcuma domestica val) and turmeric juice effect on the growth of staphylococcus aureus by invitro. This research was conducted in an integrated laboratory, FK UNUSA. The samples in this study were 4 replications per treatment. The independent variables in this study were turmeric infusion and turmeric juice (with a concentration of 10%, 30%, 50% while the dependent variable in this study was the growth of Staphylococcus aureus bacteria. Data analysis used was the one way ANOVA test and Pearson correlation to determine the effect of giving turmeric infusion and turmeric juice on the growth of bacteria staphylococcus aureus through invitro. Result: The average growth of bacteria in the turmeric infusion in group I (control), 10%, 30% and 50% of turmeric infusion was 4.89 ± 0.4425 log CFU / ml, 3.07 ± 0.61330 log CFU / ml, 2.99 ± 0.63986 log CFU. / ml and 3.02 ± 0.22650 log CFU / ml. The average growth of this bacteria in giving turmeric juice in group I (control), giving 10%, 30% and 50% turmeric infusion was 4.89 ± 0.04425 log CFU / ml, 4.40 ± 0.18355log CFU / ml, 3.10 ± 0.58926 log CFU / ml and 3.02 ± 0.38206 log CFU / ml. Conclusion: In this study, found that there was an effect of giving turmeric infusion and turmeric juice (Curcuma domestica val) on Staphylococcus aureus growth and there was an effect of giving multilevel doses of turmeric infusion and turmeric juice (Curcuma domestica val) on Staphylococcus aureus growth through invitro.